Preliminary Discrimination of Cheese Adulteration by FT-IR Spectroscopy - Lucian Cuibus; Rubén Maggio; Vlad Mureşan; Zorița Diaconeasa; Florinela Fetea; Carmen Socaciu (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2014)
The present work describes a preliminary study to compare some traditional Romanian cheeses and adulterated cheeses using Attenuated Total Reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). For PLS model calibration (6 concentration levels) and validation (5 concentration levels) sets were prepared from commercial Dalia Cheese from different manufacturers by spiking it with palm oil at concentrations ranging 2-50 % and 5-40 %, respectively. Fifteen Dalia Cheese were evaluated as external set. The spectra of each sample, after homogenization, were acquired in triplicate using a FTIR Shimatsu Prestige 21 Spectrophotometer, with a horizontal diamond ATR accessory in the MIR region 4000-600 cm-1. Statistical methods as PLS were applied using MVC1 routines written for Matlab R2010a. As first step the optimal condition for PLS model were obtained using cross-validation on the Calibration set. Spectral region in 3873-652 cm-1, and 3 PLS-factors were stated as the best conditions and showed an R2 value of 0.9338 and a relative error in the calibration of 17.2%. Then validation set was evaluated, obtaining good recovery rates (108%) and acceptable dispersion of the data (20%). The curve of actual vs. predicted values shows slope near to 1 and origin close to 0, with an R2 of 0.9695. When the external sample set was evaluated, samples F19, F21, F22 and F24, showed detectable levels of palm fats. The results proved that FTIR-PLS is a reliable non-destructive technique for a rapid quantification the level of adulteration in cheese.  The spectroscopic methods could assist the quality control authority, traders and the producers to discriminate the adulterated cheeses with palm oil.